BRONZE KELINTANG MUSIC IN TANJUNG JABUNG TIMUR REGENCY IN THE CULTURAL LANDSCAPE OF SOUTHEAST ASIA: Musik Kelintang Perunggu Di Kabupaten Tanjung Jabung Timur Dalam Lanskap Budaya Asia Tenggara - Anastasia Wiwik Swastiwi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines Bronze Kelintang Music in East Tanjung Jabung Regency within the analytical framework of the Southeast Asian cultural landscape. Although Malay musical traditions have been widely discussed in ethnomusicological studies, limited scholarship has positioned Bronze Kelintang within the broader maritime cultural configuration of Southeast Asia. This study addresses this gap by reconstructing its historical trajectories and analyzing its functional transformation within regional networks of cultural interaction. Employing historical methods with a qualitative approach, the research integrates literature review, comparative organological analysis, and socio-cultural interpretation. The findings reveal that the bronze pencon-based structure of Bronze Kelintang exhibits organological affinities with Southeast Asian gong-chime traditions, indicating cultural diffusion processes shaped by maritime trade and migration. Its function has shifted from sacred ritual contexts embedded in cosmological belief systems to representational performances in contemporary public spaces, reflecting broader socio-cultural restructuring in coastal Malay communities. Theoretically, this study contributes to Southeast Asian cultural landscape discourse by conceptualizing Bronze Kelintang as a material-cultural node that mediates local identity formation and regional interaction. This perspective extends cultural landscape analysis beyond spatial representation toward understanding musical instruments as historical markers of maritime connectivity. Contemporary challenges include limited instrument sustainability, weak regeneration, and insufficient community-based preservation mechanisms. An integrative preservation strategy that incorporates historical continuity, regional interconnectivity, and cultural policy support is therefore necessary.